A Case Report Looking at An Incidental Finding of A Partial Anomalous Pulmonary Venous Connection (PAPVC) Using Magnetic Resonance Angiography (MRA) - Iqra Qamar; Mohammad Waleed (University Library System, University of Pittsburgh, 2018)
Background: Partial anomalous pulmonary venous connection (PAPVC) is a rare congenital defect where one or more of the pulmonary veins drain to the right atrium or its tributaries. This may cause a left to right shunt (LTRS) which may need surgical management. This case looks at a 58-year-old lady  with a background of Non-ST elevation myocardial infarction (NSTEMI) and co-morbidities, who presented with central chest pain. Cardiac magnetic resonance angiogram (MRA) was used in the  diagnosis and management of her PAPVC. Results: On MRA an incidental finding of PAPVC was found (left upper pulmonary vein drained into brachiocephalic vein) creating a LTRS which wasn't substantial (Qp/Qs <1.5). Delayed hyper-enhancement of the septal regions indicated a myocardial infarction, however the right and left ventricles remained unremarkable. Despite being asymptomatic, this patient was followed up, with informed consent, and if symptoms developed, she would be considered for PAPVC surgery. Conclusion: Studies showed PAPVC patients developing symptoms or LTRS as candidates for operation. However, the issue lied in using multimodality imaging to diagnose the PAPVC, as one modality was insufficient. Physicians should be aware of rare anomalies like PAPVC and should follow up these patients closely in case of worsening of the LTRS, in which case surgical correction may be possible. Overall, PAPVC i) can be overlooked ii) diagnosis requires multimodality imaging iii) constant follow up and iv) may be operable.